SPS147 - Professional Activity (Swimming and Track & Field) / Faculty of Sports Science & Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2018)
Professional Activity on Swimming and Track & Field. At the end of the course, students should be able to discuss fundamental principles, concepts and theories in swimming and track and field.